2018
DOI: 10.1186/s13065-018-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of characteristic aroma compounds in raw and thermally processed African giant snail (Achatina fulica)

Abstract: BackgroundFood flavor appreciation is one of the first signals along with food appearance and texture encountered by consumers during eating of food. Also, it is well known that flavor can strongly influence consumer’s acceptability judgment. The increase in the consumption of snail meat across the world calls for the need to research into the aroma compounds responsible for the distinctive aroma notes of processed snail meat.ResultsThe odorants responsible for the unique aroma notes in thermally processed gia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Generally, the freeze-dried samples were more preferred to the smoked samples in all the attributes assessed (Figure 3). This affirms earlier reports that freeze-drying preserves sensory properties of products because of the low temperatures involved [8]. It was also observed that the 15 h freeze-dried half-sized samples were the most liked in all the sensory attributes assessed, except for aroma where the 25 h freeze-dried whole samples were the most liked.…”
Section: Sensory Evaluationsupporting
confidence: 90%
See 1 more Smart Citation
“…Generally, the freeze-dried samples were more preferred to the smoked samples in all the attributes assessed (Figure 3). This affirms earlier reports that freeze-drying preserves sensory properties of products because of the low temperatures involved [8]. It was also observed that the 15 h freeze-dried half-sized samples were the most liked in all the sensory attributes assessed, except for aroma where the 25 h freeze-dried whole samples were the most liked.…”
Section: Sensory Evaluationsupporting
confidence: 90%
“…Snail meat is rich in protein (about 80.9-89.92% on dry basis) and low in fat and cholesterol [6,7] positioning it as a good protein source for health-conscious consumers. The meat of the snail is characteristically tender and chewy, with a unique pleasant floral-like, mushroom-like flavour when boiled [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter work, sotolone was revealed as the key aroma compound in a blanched Norway lobster, while in other studies, furaneol was found in beef broth. Moreover, the furaneol content in the roasted goose’s leg meat (633 μg/kg) was the greatest from among the roasted and fried meat of other animals (fried chicken meat, 50 μg/kg; fried giant snail meat, 46.5 μg/kg; and roasted duck meat, not detected).…”
Section: Resultsmentioning
confidence: 66%
“…Blending with SMP also lead to a smooth dough consistency during kneading that increased pore formation in crumb after baking bringing about sponginess, fine crumb, and crumby texture of buns (Agengo et al., 2020a ). The cooked mushroom, roasted meat, and fried fish flavor and aroma in buns may have been activated by thermal activities on odorants such as 1‐octen‐3‐one, 2‐acetylthiazole and tetradecanal present in processed snail meat (Lasekan et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%